Pengembangan Media Pembelajaran Berbasis Problem Solving Menggunakan Aplikasi Genially pada Materi Bangun Datar Kelas V - Annisa Khadijah Shalimar; Rukmana , Diki (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
The lack of digital learning media and students' unfamiliarity with doing exercises without any thought process in solving the problems resulted in students' lower numeracy skills. This study aims to develop digital media using the Genial application as a mathematics learning tool to increase fifth-grade students' learning interest and problem-solving skills at a Public Elementary School in Central Jakarta in the 2024/2025 academic year. The research method used is R&D (Research and Development) with the ADDIE model. Data were collected through interviews, observations, and questionnaires and then analyzed quantitatively and qualitatively. This study was validated by a Mathematics material expert, a media expert, a linguist, one teacher, and 23 fifth-grade elementary school students. The validation results showed a score of 90% from material experts, 96% from media experts, 100% from linguists, 100% from teachers, and 85% from students. The T-test showed the Asiymp Sig value. (2-tailed) <0.001 indicates a significant difference in problem-solving abilities between class VA students who use the genial application and class VB students who do not.